Lathe Workshop Layout Design Analysis Using Blocplan and SLP Methods - Jeffri; Tarigan, Uni Pratama Pebrina; Sembiring, Anita Christine (TALENTA Publisher, 2024)
An inappropriate layout can result in excessive material movement and increase costs significantly. Therefore, it is important to carefully plan the facility layout so that related activities can be coordinated according to the applicable departments and workflows. Sinar Abadi Lathe Workshop is a company engaged in the machining business, especially in the lathe process. This process involves working with materials by cutting or modifying workpieces using a lathe. This research analyses the layout of the lathe workshop using the SLP and BLOCPLAN methods in order to reduce moving costs, and optimism the use of space in the context of the lathe workshop. The implementation of the BLOCPLAN method in the lathe shop showed labor efficiency with less labor required per production cycle compared to the initial layout. However, a complete change from the original layout may result in higher moving costs. This highlights the importance of cost considerations in choosing a layout method. For layout changes with minimal moving costs, the SLP Layout is proposed as a cost-efficient alternative, as it considers various factors, including distance, material transportation, and labor requirements in planning the layout.